Two-color single-molecule tracking in live cells - Hänselmann, Siegfried; Herten, Dirk-Peter (Super-resolution microscopy, 2017)
Measuring the kinetics of protein-protein interactions between molecules in the plasma membrane of live cells provides valuable information for understanding dynamic processes, like cellular signaling, on a molecular scale. Two-color single-molecule tracking is a fluorescence microscopy-based method to detect and quantify specific protein-protein interactions on a single-event level, providing sensitivity to heterogeneities and rare events. Fundamentally, it allows following the movement of single molecules of two different protein species in live cells with a localization precision beyond the diffraction limit of light in real time. It hence provides information about the diffusion behavior of every protein as well as about their dimerization kinetics. Here, we describe all the necessary steps to obtain two-color tracking data of plasma membrane-associated proteins in live cells using SNAP-tag and HaloTag fusion constructs and total internal reflection fluorescence (TIRF) microscopy. Also, we outline the main steps needed for analyzing the recorded data.
Gesehen am 26.07.2018